ANALISIS ARKEOBOTANI DALAM PENELITIAN ARKEOLOGI - Siswanto (BRIN, 2000)
Flora residue in any form for archaeological studies will generally be directly related to past humans, namely regarding food sources, plant cultivation or agricultural culture, and technology. The rest is related to past environmental and vegetation problems (archaeo-ecology), dating interests, climatology, and others. Experts have developed many techniques and methods for handling the findings of flora residue. However, the Puslit Arkenas has not been fully utilized, this is in addition to limited human resources as well as its supporting tools. Efforts to overcome deficiencies can be done through cooperation with external parties.